Relationship between mammary papillomatosis and mastitis in cows - Ali Rişvanlı; Cahit Kalkan (Eurasian Journal of Veterinary Sciences)
The aim of this study was to investigate the relationship between mammary papillomatosis and mastitis in cows. A total of 1249 cows (396 Brown-Swiss, 338 Holstein, 31 Simental. 355 hybrid. 6 Jersey and 123 local strain) aged between 2-16 were used as subjects. The presence of mastitis was determined by clinical examination, CMT and microbiological examinations. Then, this data were compared with mammary papillomatosis rates. In conclusion, il was determined that the incidence of mammary papillomatosis was 13.37%. In 45.99 percent of these cows, papillomatosis were accompanied with mastitis. However, the rate of mastitis was higher in Simmental breed cows with papillomatosis than other breeds. The incidence of mammary papillomatosis was low in Jersey breed cows. Additional, mammary papillomatosis was found to be lowest in cows of 2-4 aged group. There was no difference between cows regarding to the rale of mastitis when their ages were considered.